PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE GLAD2GLOW - Anisa Aliefia Putri; Marifa Ramadhini Hartanti; Eka Ayu Rahmawati (Cahaya Ilmu Bangsa, 2024)
With the increasing awareness of the importance of skincare, the skincare industry has grown rapidly. In this competitive market, customers want products that are not only affordable but also high-quality, safe, and can meet their needs well. As a result, price and product quality are the main factors in choosing a product. The study aims to find out how the quality and price of Glad2Glow skincare products affect buyer decisions. A survey was conducted on users who have used the product, and data was collected and analyzed to find out how the variables studied are related to each other. The results showed that price has a significant effect on product purchasing decisions, but product quality has a positive and significant effect. The results show that customers prioritize quality over price when choosing skincare products. Therefore, to increase customer attraction and loyalty, businesses must concentrate on improving product quality and building a strong brand image.